Longitudinal analysis of adolescent girls’ activity patterns in San Diego and Minneapolis: Understanding the influence of the transition to licensure - McDonald, Noreen; Merlin, Louis A.; Hu, Haoting; Shih, Joshu; Cohen, Deborah; Evenson, Kelly; McKenzie, Thomas; Rodriguez, Daniel (Journal of Transport and Land Use, 2015)
The proportion of teens and young adults with driver’s licenses has declined sharply in many industrialized countries including the United States. Explanations for this decline have ranged from the introduction of graduated driver licensing programs to the increase in online social interaction. We used a longitudinal cohort study of teenage girls in San Diego and Minneapolis to evaluate factors associated with licensure and whether teens’ travel patterns become more independent as they age. We found that licensure depended not only on age but also on race and ethnicity as well as on variables that correlate with household income. Results also showed evidence that teen travel became more independent as teens aged, and that acquiring a license is an important part of this increased independence. However, we found limited evidence that teens’ travel-activity patterns changed as a result of acquiring a driver’s license. Rather, teen independence resulted in less parental chauffeuring but little shift in travel patterns. For the larger debate on declining millennial mobility, our results suggest the need for more nuanced attention to variation across demographic groups and consideration of the equity implications if declines in travel and licensure are concentrated in low-income and minority populations.